Главная

Алгебра 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

ГДЗ учебник по алгебрее 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г.

Раздел:

Номер №698

Найдите корень уравнения:
а)
$5 + x^2 = (x + 1)(x + 6)$
;
б) 2x(x − 8) = (x + 1)(2x − 3);
в) (3x − 2)(x + 4) − 3(x + 5)(x − 1) = 0;
г)
$x^2 + x(6x - 2x) = (x - 1)(2 - x) - 2$
.

Решение а

$5 + x^2 = (x + 1)(x + 6)$

$5 + x^2 = x^2 + 6x + x + 6$

$x^2 - x^2 - 6x - x = 6 - 5$

7x = 1
$x = -\frac{1}{7}$

Решение б

$2x(x - 8) = (x + 1)(2x - 3)$

$2x^2 - 16x = 2x^2 - 3x + 2x - 3$

$2x^2 - 16x - 2x^2 + 3x - 2x = -3$

15x = −3
$x = \frac{3}{15} = \frac{1}{5}$

Решение в

$(3x - 2)(x + 4) - 3(x + 5)(x - 1) = 0$

$3x^2 + 12x - 2x - 8 - 3(x^2 - x + 5x - 5) = 0$

$3x^2 + 10x - 8 - 3(x^2 + 4x - 5) = 0$

$3x^2 + 10x - 8 - 3x^2 - 12x + 15 = 0$

2x = − 7
$x = \frac{7}{2} = 3\frac{1}{2}$

Решение г

$x^2 + x(6x - 2x) = (x - 1)(2 - x) - 2$

$x^2 + 6x - 2x^2 = (2x - x^2 - 2 + x) - 2$

$x^2 + 6x - 2x^2 = 3x - x^2 - 4$

$x^2 + 6x - 2x^2 - x + x^2 = -4$

3x = −4
$x = -\frac{4}{3} = -1\frac{1}{3}$